High School Tv. viewing and alienation: an exploratory study of a synthesis model - Dvorak, Anthony John (My University, 1974)
This thesis is both empirical and theoretical, as well as specific and general. We were determined not to have just an empirical study, as we see no value in doing empirical studies that lack solid theoretical support. And as we found most alienation studies to lack a sound theoretical base, our theoretical purpose was to establish a conceptual model that would eliminate this problem. Hence we began with a critical appraisal of several theories of alienation, bringing to light all the problems regarding definitions, causes, consequences and validity dilemmas. To solve these we next developed a new model which viewed alienation as a process, and through a synthesis we were able, by now using this new model, to crystallize alienation into a specific concept. However logical a model mlght sound, it must be tested in practice. Hence we established a specific research problem. We wanted to test whether the television medium is used as a mechanism of escape from the viewers' feelings of alienation. Furthermore, we also wanted to see whether the model generally works.
In conclusion the model was not rejected after the data analysis since the predictd variable relationships were confirmed totally or in part. We then offered several lines that future research should take in using this model. With regards to our specific problem, we did find a positive relationship between escapist television (high amount of watching for escapist reasons) and certain attitudinal properties found in the second stage of our alienation model.
Keywords: Sociology; Sociology